El uso del software educativo como recurso didáctico en el proceso enseñanza aprendizaje - Carrión Cabrera, Arturo David (MACHALA, 2019)
In the Knowledge Society, in order to have efficient, effective and effective teaching-learning processes, it has been assumed the use of Information Communication Technologies within the classroom in analogous and digital environments, which has meant the revaluation and resignification of the use of educational software as a didactic resource to work subjects in areas transverse to the curriculum. The present research work analyzes the use of educational software through a bibliographic review of authors specialized in the subject-object of study. As a result, we can see the great dominance of the use of educational software by students, which has improved their autonomous, independent and self-regulated learning processes.
En la Sociedad del Conocimiento, para tener procesos de enseñanza-aprendizaje eficientes, eficaces y efectivos se ha asumido el uso de las Tecnologías de la Información Comunicación dentro del salón de clases en ambientes análogos y digitales, lo que ha significado la revalorización y resignificación del uso del software educativo como recurso didáctico para trabajar asignaturas en áreas transversales al currículo. El presente trabajo de investigación analiza el uso del software educativo a través de una revisión bibliográfica de autores especializados en el tema-objeto de estudio. Como resultado, se advierte el gran dominio del uso del software educativo por parte de los discentes lo que ha mejorado sus procesos de aprendizaje autónomo, independiente y autorregulado.
Keywords: EDUCATIONAL SOFTWARE; TEACHING-LEARNING PROCESS; AUTONOMOUS LEARNING